2003
DOI: 10.1089/089771503765172291
|View full text |Cite
|
Sign up to set email alerts
|

Tempol, a Novel Stable Nitroxide, Reduces Brain Damage and Free Radical Production, after Acute Subdural Hematoma in the Rat

Abstract: Recent studies have shown that there is increased production of deleterious free radicals following acute subdural hematoma (ASDH). Scavenging them may therefore be of therapeutic benefit. Nitroxides are new, low molecular weight, cell permeable superoxide dismutase mimics. This study investigated the neuroprotective effect of 4-hydroxy-2,2,6,6-tetramethylpiperidine-1-oxyl (Tempol) following ASDH in the rat. Twenty-one male Sprague-Dawley rats were used in two studies: (1) a volumetric study of ischemic brain … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0
1

Year Published

2004
2004
2016
2016

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(22 citation statements)
references
References 50 publications
1
20
0
1
Order By: Relevance
“…43 It has also been shown that addition of pharmacological antioxidants during T-cell activation in vitro can augment activation of extracellular signal-regulated kinase, coinciding with decreases in T-cell apoptosis. 44,45 In conclusion, the present results indicate that the activation phenotype, survival and function of antigenspecific T cells can be differentially modulated by TQ concentrations. At low concentration, TQ not only directly modulates the expression of CD62L on activated CD8 + T cells but also selectively promotes the survival and function of activated CD8 + T cells that express high levels of CD62L.…”
Section: Discussionsupporting
confidence: 51%
“…43 It has also been shown that addition of pharmacological antioxidants during T-cell activation in vitro can augment activation of extracellular signal-regulated kinase, coinciding with decreases in T-cell apoptosis. 44,45 In conclusion, the present results indicate that the activation phenotype, survival and function of antigenspecific T cells can be differentially modulated by TQ concentrations. At low concentration, TQ not only directly modulates the expression of CD62L on activated CD8 + T cells but also selectively promotes the survival and function of activated CD8 + T cells that express high levels of CD62L.…”
Section: Discussionsupporting
confidence: 51%
“…), and the carbonate radical (CO 3 .À ) (Augusto et al, 2008). Tempol readily crosses the BBB (Zhelev et al, 2009), and has previously been shown to provide neuroprotection as a free radical scavenger in several models of brain injury and ischemia (Kwon et al, 2003;Deng-Bryant et al, 2008;Rak et al, 2000;Cuzzocrea et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Acute subdural hematoma can also result in local cerebral ischemia and O 2 • − mediated damage. Tempol administration resulted in a 42% decrease in infarct size and 2,3-dihydrobenzoic acid levels in rats following experimentally induced subdural hematoma [72]. Similar trials studying renal protection were performed by clamping the renal pedicle in rats and Tempol again had a protective effect on kidney function after reperfusion [73].…”
Section: Ischemia-reperfusion Injury and Inflammationmentioning
confidence: 99%